DIALOGUE AS EDUCATIONAL MEETING IN THE CONTEXT OF SOCIAL WORK - Kiaunytė, Asta; Puidokienė, Dalia (Acta Paedagogica Vilnensia, 2011)
This article is an update of the dialogue and its educational power in a professional relation of social work in the system of mutual interaction: the client –the social worker-the supervisor. The problem is revealed in the context of complex realities of social work, reflecting on trends of postmodern society. Dialogue as an educational meeting is analyzed in perspectives of philosophical, sociological and educational theoretical concepts. The review of accomplished scientific research supposes the new problematical questions, which are examined in this article: what are the characteristics of a dialogue as an educational meeting in a professional relation? What does the dialogical relation give and why it is important in the mutual interaction of social worker-client? What are the characteristics and what does the dialogical process of the supervisions provide? The object of this analysis is the dialogue as educational meeting in the context of social work. The object is examined applying the analysis of scientific sources, synthesis and interpretation. Authors of the article point out, that the core of the dialogue as educational meeting is to acknowledge and to be able to understand emphatically the other world of a client and to operate in the indeterminate situations of social work. The dialogue in the professional relation of social work becomes significant not only in a professional (social worker, supervisor) and the client dyad, but also is shrouding the client – social worker – supervisor triad, as an entire whole help process. Supervision as the professional activity of social work using the process of dialogue promotes reflection and new action in practice. Dialogical process of supervision characterizes tolerance, professional curiosity, when there is no need to know but there is a will to know, looking for multidimensity of supervised situation. Summing up, the dialogue used in practice of social work provides the opportunity to see otherness in the social phenomenon, to recognize diversity, to accept a version of truth, to construct a new knowledge and to adjust oneself and ones own relationship with the world, finding a new meanings.